2020
DOI: 10.1021/acs.jpcc.0c01465
|View full text |Cite
|
Sign up to set email alerts
|

Band Engineering for Realizing Large Effective Mass in Cu3SbSe4 by Sn/La Codoping

Abstract: How to further improve the thermoelectric performance in Cu3SbSe4-based materials after optimizing its carrier concentration is a difficult issue. The present study attempts to address the issue by investigating thermoelectric performance of Cu3SbSe4 after Sn and La codoping, and all the samples were obtained by using a microwave-assisted hydrothermal synthesis method followed with the spark plasma sintering (SPS) process. First, a series of Cu3Sb1–x Sn x Se4 (x = 0–0.03) compounds have been synthesized, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…Assuming that acoustic phonon scattering is dominant, the single parabolic band model was employed to analyze the electrical transport data by using the Pisarenko plot (Figure 4e), which reveals that the density state of effective mass in Cu 3 SbSe 4 −xCuAlSe 2 composites is around 2.0m e . Such an m d * value is comparable to that for other Cu 3 SbSe 4 -based compounds in literature, [32][33][34][36][37][38]47,48,54] which manifests the fact that the compositing only enlarges the hole concentration while has no evident influence on band structure. The weighted mobility is an important parameter that characterizes the intrinsic electrical property of TE materials.…”
Section: Electrical Transport Propertysupporting
confidence: 69%
See 3 more Smart Citations
“…Assuming that acoustic phonon scattering is dominant, the single parabolic band model was employed to analyze the electrical transport data by using the Pisarenko plot (Figure 4e), which reveals that the density state of effective mass in Cu 3 SbSe 4 −xCuAlSe 2 composites is around 2.0m e . Such an m d * value is comparable to that for other Cu 3 SbSe 4 -based compounds in literature, [32][33][34][36][37][38]47,48,54] which manifests the fact that the compositing only enlarges the hole concentration while has no evident influence on band structure. The weighted mobility is an important parameter that characterizes the intrinsic electrical property of TE materials.…”
Section: Electrical Transport Propertysupporting
confidence: 69%
“…It is observed that the weighted mobility increases slightly with increasing CuAlSe 2 content at room temperature and finally converges at high temperature. In this section, it is concluded that the superior electrical performance of Cu 3 SbSe 4 −xCuAlSe 2 composites results from [32][33][34][36][37][38]47,48,54] f) Weighted mobility as a function of temperature.…”
Section: Electrical Transport Propertymentioning
confidence: 99%
See 2 more Smart Citations
“…(The calculation formula is in the Supporting Information.) It can be seen from the figure that the effective mass 33,34 of the doped samples is significantly higher than that of the undoped CuGaTe 2 , which is due to the degeneracy of the band 35 and the increase in the electron density of states near the Fermi level 30 after the introduction of Zn. At the same time, the band between the point Z− and the point X− in the Brillouin zone becomes slightly flat, which is consistent with the theoretical value of the calculated band, making the effective mass of the (CuGaTe 2 ) 1−x (2ZnTe) x samples higher than that of the pure phase CuGaTe 2 under the same carrier concentration.…”
Section: Resultsmentioning
confidence: 92%